Sleep hygiene and sleep quality among yoga and naturopathy medical students in India: a multisite cross-sectional study - Silwal, Karishma; Kodali, Prakash Babu; Sharma, Hemanshu; Ajit, Nair Dhiren; Shankaregowda, Abhay M.; Mohanan, Renjish; Subha, M. Jerin; Vibhas, K.; Sivaraman, S.; Bhalavat, Kinjal; Dhilip, V. R.; Nair, Jyoti; et al. (Frontiers in Sleep, 2025)
IntroductionPoor sleep quality and sleep hygiene among medical students is a concern, with limited data on students from alternative medical systems.MethodsThis cross-sectional study assessed 1,151 undergraduate yoga and naturopathy medical students from 10 Indian colleges. A structured questionnaire was used to collect sociodemographic and lifestyle data, while sleep quality, sleep hygiene, depression, anxiety, stress, and Internet addiction were evaluated using the Pittsburgh Sleep Quality Index (PSQI), the Sleep Hygiene Index (SHI), the Depression Anxiety Stress Scale (DASS-21), and the Internet Addiction Test (IAT). Logistic regression models were employed to compute adjusted odds ratios (AORs) as measures of association.ResultsThe average SHI and PSQI scores were 22.49 (±6.34) and 6.52 (±3.01), respectively. Poor sleep quality was reported by 59.8 and 24.7% had poor sleep hygiene. Severe depression (AOR = 5.15) and anxiety (AOR = 2.31) were linked to poor sleep hygiene, while severe stress (AOR = 0.55) was associated with poor sleep quality. Family residence was linked to lower odds of poor sleep hygiene (AOR = 0.14 for male participants, AOR = 0.26 for female participants) and better sleep quality (AOR = 1.46). Poor sleep hygiene was associated with sugary beverage consumption (AOR = 2.02), fried/packaged foods (AOR = 5.06 weekly, AOR = 8.52 daily), Internet addiction (AOR = 21.87 for male participants, AOR = 9.57 for female participants), and late device use (AOR = 3.80 for female participants).DiscussionDespite early exposure to lifestyle principles, yoga and naturopathy students experience poor sleep quality. Contributing factors include poor sleep hygiene, anxiety, stress, unhealthy eating habits, and Internet addiction. Targeted interventions are needed to improve sleep hygiene and overall wellbeing.